US Emergency Department Visits for Acute Harms From Prescription Opioid Use, 2016–2017. - Lovegrove, Maribeth C.; Dowell, Deborah; Geller, Andrew I.; Goring, Sandra K.; Rose, Kathleen O.; Weidle, Nina J.; Budnitz, Daniel S. (American Journal of Public Health, 2019)
Objectives. To estimate the number of US emergency department visits for prescription opioid harms by patient characteristics, intent, clinical manifestations, and active ingredient. Methods. We used data from medical record–based surveillance from a nationally representative 60-hospital sample. Results. Based on 7769 cases, there were 267 020 estimated emergency department visits annually (95% confidence interval [CI] = 209 833, 324 206) for prescription opioid harms from 2016 to 2017. Nearly half of visits (47.6%; 95% CI = 40.8%, 54.4%) were attributable to nonmedical opioid use, 38.9% (95% CI = 32.9%, 44.8%) to therapeutic use, and 13.5% (95% CI = 11.0%, 16.0%) to self-harm. Co-implication with other pharmaceuticals and concurrent illicit drug and alcohol use were common; prescription opioids alone were implicated in 31.5% (95% CI = 27.2%, 35.8%) of nonmedical use visits and 19.7% (95% CI = 15.7%, 23.7%) of self-harm visits. Unresponsiveness or cardiorespiratory failure (30.0%) and altered mental status (35.7%) were common in nonmedical use visits. Gastrointestinal effects (30.4%) were common in therapeutic use visits. Oxycodone was implicated in more than one third of visits across intents. Conclusions. Morbidity data can help target interventions, such as dispensing naloxone to family and friends of those with serious overdose, and screening and treatment of substance use disorder when opioids are prescribed long-term.